Analisis Kelayakan Pembelian Saham PT Wijaya Karya (Persero), Tbk (WIKA) (Telah dipresentasikan pada The 4th National Investment Day Stock Analysis Competition) - Lufthia Sevriana; Tia Yuliawati; Ferry Tri Mulyana; Iqbal Abdul Rahman; Fadhlani Kalia (Universitas Islam Bandung, 2018)
ABSTRACT The Infrastructure Sector is one of the sectors that is the priority of the current government's attention. WIKA's shares as one of the BUMNs in Indonesia are in great demand for investors. From the results of the analysis using secondary data and descriptive methods, we recommend prospective investors to INVEST in PT WIKA's shares because the final results of various financial ratios show a positive trend and benefit investors. Solvability ratio (Debt to Total Asset Ratio) shows an upward trend which means the company is able to pay off long-term debt. The Activity Ratio (Asset Turnover Ratio) in the last few years shows that the trend is above the initial position, meaning that the company is able to manage assets well so that it generates revenue. The Net Profit Margin shows a downward trend due to several large development projects that have not been completed in the near future. Lastly, the Market Ratio (Earning Per Share) shows an increasing trend from the beginning, meaning that the longer it is kept, Every sheet of WIKA shares gives benefits to its owner.ABSTRAK Sektor Infrastruktur merupakan salah satu sektor yang menjadi prioritas perhatian pemerintahan saat ini. Saham WIKA sebagai salah satu BUMN di Indonesia banyak diminati untuk dibeli oleh investor. Dari hasil analisis menggunakan data sekunder dan metode deskriptif, kami merekomendasikan calon investor untuk BERINVESTASI pada saham PT WIKA dikarenakan hasil akhir dari berbagai rasio keuangan menunjukkan trend yang positif dan menguntungkan investor. Rasio Solvabilitas (Debt to Total Asset Ratio) menunjukkan trend meningkat yang artinya perusahaan mampu melunasi hutang jangka panjang. Rasio Aktivitas (Rasio Perputaran Aktiva) pada beberapa tahun terakhir menunjukkan trend berada di atas posisi awal artinya perusahaan mampu mengelola asset dengan baik sehingga menghasilkan pendapatan. Rasio Profitabilitas yang (Net Profit Margin) menunjukkan trend menurun dikarenakan beberapa proyek pembangunan besar yang belum rampung dalam waktu dekat. Terakhir, Rasio Pasar (Earning Per Share) menunjukkan trend peningkatan dari sejak awal, artinya semakin lama disimpan, Setiap lembar saham WIKA memberi keuntungan bagi pemiliknya.